On the Occurrence of Pomatiopsis Cincinnatiensis in Wisconsin - Lowell L. Getz (Hello World!, 1971)
Baker (1928: 169-170) indicated that the prosobranch snail, Pomatiopsis cincinnatiensis (Lea), had not been recorded from Wisconsin but indicated 'there is not the slightest doubt that it will sooner or later be found on Wisconsin soil' because of 'its abundance in northeastern Illinois.' A search of the literature indicated no subsequent record of the species in Wisconsin, however.